Jenny Thompson at 80 m of Her World Record 100 m Race at the 1999 Pan Pacific Championships in Sydney - Rushall, B. S. (1999)
Video pictures (24 frames) and the appropriate technical/ biomechanical explanations for Jenny Thompson at 80 m of Her World Record 100 m Race at the 1999 Pan Pacific Championships in Sydney.